"I don't know how to fix it and sometimes it's so overwhelming" Identifying the barriers and facilitators for family caregivers supporting someone at high-risk of psychosis: A qualitative study. Issue 1 (2nd January 2020) - Izon, Emma; Berry, Katherine; Law, Heather; Au-Yeung, Karmen; French, Paul
ABSTRACT: Providing care can be demanding and is associated with increased financial, emotional and psychological distress. Relatives of individuals with At-Risk Mental State (ARMS) of psychosis provide significant emotional, practical and economic support but are often a neglected group. The current study aimed to investigate the barriers and facilitators for those supporting ARMS individuals. Semi-structured interviews with fourteen family members from the Individual and Family Cognitive Behavioural Therapy (IFCBT) trial were conducted. Key barriers included relatives' unmet needs and limited confidence accessing and providing support. Facilitating factors included open communication with the individual, flexible, understanding employers and feeling that they themselves were supported. Those who identify multiple barriers may have increased levels of worry and distress that negatively impact their own health and wellbeing. Services in contact with ARMS individuals should provide families support to sustain an adequate level of care, including psychoeducation around the individual's experiences and behaviours, discussions around talking to employers and help exploring more adaptive coping strategies including accessing support from social networks. Clinical teams and/or family peer-support workers that look to support relatives early in their caregiving journey could help improve outcomes in relative's quality of life and consequently benefit the ARMS individual.